Visitation patterns of jaguars Panthera onca (Carnivora: Felidae) to isolated water ponds in a tropical forest landscape - Gaitán, Carlos A.; González-Castillo, Vivian R.; Guzmán-Flores, Gerber D.; Aguilera, Andrea L.; García, Manolo J. (THERYA, 2020)
Jaguar populations have declined dramatically in the last century. The Maya Biosphere Reserve (MBR) within the Selva Maya (SM) is a priority area for jaguar conservation. Influential factors in the jaguar seasonal distribution include the availability of surface water in wetlands such as the â€œaguadasâ€ and the availability of prey. Aguadas are formed by isolated depressions in the landscape and serve as a water supply for wildlife during dry periods. The goal of this study was to describe the visitation patterns of jaguars to aguadas in a Tropical forest at Dos Lagunas Protected Biotopo, a core zone of the MBR, Guatemala. We used camera-trap data from seven aguadas during the dry seasons 2014-2017. We determined visitation rates (VR, records for 1,000 trap-days) and activity patterns (AP) of jaguars for all years, aguadas, and sexes. We tested for significant differences in AP between sexes, and we estimated the coefficient of overlap (D) for female and male jaguar activity. We recorded 14 individuals (five females, eight males, and one unsexed) in 60 visit events. Jaguars have significant more diurnal activity at aguadas, and showed a VR = 13.1 for 1,000 trap-days. VR varied between aguadas (VR = 9.5 â€“ 19.4), years (VR = 1.9 â€“ 39.2) and sexes (VR = 6.1 for females and 5.5 for males). We did not find significant differences in the AP of female and male jaguars (P > 0.05). The coefficient of overlap between activity of females and males was D = 0.77 (95 % confidence interval: 0.70 to 0.84; P > 0.05). Aguadas may represent regular sites of jaguar home-ranges overlap for the important resources they provide for wildlife during the dry season. Aguadas could play an important role in the conservation and management of jaguar populations since the spatial distribution of these bodies of water is scattered, but ecologically important for jaguars within the MBR and the SM. Aguadas also, are important landscape features that could influence the spatial interactions of individuals. We encourage jaguar researchers to increase investigation on jaguars visiting aguadas and other wetlands in the SM to better understand the jaguar activity patterns and sex-specific habitat requirements.